Багатомірне нелінійне управління випарними установками - Уліцька, О. О.; Стопакевич, О. А. (Видавництво Львівської політехніки, 2011)
The multivariable nonlinear control system of sugar industry multiple-unit evaporator, which belongs to affine class system, was developed and investigated at first. The application of nonlinear control systems allows increasing equipment work load range and transferring it to new stage, providing steady work.
Keywords: nonlinear controller; control system; affine system; evaporator